2021
DOI: 10.1016/j.hroo.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low-level electromagnetic fields on the inducibility of atrial fibrillation in the electrophysiology laboratory

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Further, it has been shown that AF progression through cellular remodeling could be reduced by minimizing sympathetic or increasing parasympathetic tone ( Bashir et al, 2019 ). In a recent study ( Sohinki et al, 2021 ), investigated the impact of low-level electromagnetic fields (LL-EMF) which is specifically targeted for vagal stimulation, on AF inducibility in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been shown that AF progression through cellular remodeling could be reduced by minimizing sympathetic or increasing parasympathetic tone ( Bashir et al, 2019 ). In a recent study ( Sohinki et al, 2021 ), investigated the impact of low-level electromagnetic fields (LL-EMF) which is specifically targeted for vagal stimulation, on AF inducibility in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Sohinki et al recently investigated the ability of LL-EMF to attenuate pacing-induced AF in patients presenting for AF ablation. 66 In response to 60 min of LL-EMF stimulation applied over the head and neck, they were able to demonstrate reductions in the duration of pacing-induced AF (11.0 ± 3.43 min; P = .03), ectopic firing initiating spontaneous episodes of AF, and reductions in levels of the chemoattractant molecule monocyte chemoattractant protein-1. 66 …”
Section: Low-level Electromagnetic Field Applicationmentioning
confidence: 94%
“…The study showed that external EMF (applied around the head) with a strength of 0.032 μG at a frequency of 0.89 Hz, applied before ablation, could suppress the inducibility of AF. 72 Based on the proof-of-concept studies conducted, EMF appears to be a promising noninvasive approach to managing AF by inhibiting the activity of extrinsic and intrinsic cardiac ANS. However, more large-scale human studies are necessary to evaluate its efficacy in improving clinical outcomes for AF.…”
Section: Modulation Of the Autonomic Nervous Systemmentioning
confidence: 99%
“…EMF was applied to the bodies of the patients to influence the neural networks that innervate the heart. The study showed that external EMF (applied around the head) with a strength of 0.032 μG at a frequency of 0.89 Hz, applied before ablation, could suppress the inducibility of AF 72 . Based on the proof‐of‐concept studies conducted, EMF appears to be a promising noninvasive approach to managing AF by inhibiting the activity of extrinsic and intrinsic cardiac ANS.…”
Section: Therapeutic Value Of Emf‐based Modalitiesmentioning
confidence: 99%